Pengembangan Lembar Kerja Peserta Didik (LKPD) Matematika Berbasis Pendekatan Contextual Teaching and Learning (CTL) dengan Menggunakan Media Canva - Ulya, Khairatul; Srimuliati, Srimuliati; Alviona, Nabila; Khairi, Nabila Luthfiyyah; Tryandini Putri, Natasya (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
This research aims to develop CTL-based LKPD on trigonometry material using Canva. This research uses Research and Development (R&D) with the ADDIE model, namely Analysis, Design, Development, Implementation and Evaluation. The instrument used is an independent guide according to the textbook which provides special instructions to help students complete the stages in the trigonometrical function. The product feasibility test stage was carried out by three experts, namely material experts, media experts and design experts. The results of this development show that the product validity value is in the valid category and the practicality value in the very practical category. So it can be concluded that the LKPD developed with the CTL stage using the Canva application is valid and very practical so it is suitable to be used as teaching material to help students understand the material regarding trigonometric functions.